Solid electrolyte membrane, preparation method thereof and battery
By using a combination of copolymer polyimide arachnoid membrane and a high ionic conductivity sulfide solid electrolyte, the problem of dry binder instability was solved, and a solid electrolyte membrane with high conductivity and structural strength was prepared to improve the The performance and stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202411627906.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-07
AI Technical Summary
The binder of the existing dry solid electrolyte membrane is unstable at low potential and is prone to irreversible reaction with lithium, causing the solid electrolyte membrane to collapse loosely, reduce the bonding effect, and affect battery performance.
Using copolymer polyimide arachnoid membrane as a binder, combining sulfide solid electrolyte with high ionic conductivity, solid electrolyte membrane is prepared by kneading, extrusion and thinning treatment to ensure high structural strength at low content and electrical insulation properties.
The high ionic conductivity, excellent electrical insulation performance and structural stability of the solid electrolyte membrane are achieved, the energy density and cyclic stability of the battery are improved, and the side reactions of the solvent and the increase in energy consumption are avoided.
Smart Images

Figure BDA0005135192530000091 
Figure BDA0005135192530000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a solid electrolyte membrane and a preparation method thereof, and a battery. Background Art
[0002] Lithium-ion batteries have been widely used in various portable electronic products (such as laptops, mobile phones and digital cameras) and electric vehicles. However, since traditional lithium-ion batteries need to use flammable organic solvents as electrolytes, there are great safety risks. In comparison, solid-state lithium-ion batteries using solid electrolytes have greater safety advantages. At the same time, the solid electrolyte membrane in the solid-state battery can act as an electrolyte for transmitting lithium ions, and can also serve as a diaphragm to block the contact between the positive and negative electrodes, which can significantly improve the energy density of lithium-ion batteries.
[0003] The solid electrolyte used in solid-state batteries is generally an inorganic powder. To prepare the solid electrolyte powder into a solid electrolyte membrane, a binder needs to be added to it to bond the loose powder particles into a whole. The binder is generally a polymer.
[0004] There are two methods for preparing solid electrolyte membranes, namely wet method and dry method. The wet method usually involves dissolving and dispersing the polymer binder in an organic solvent, then adding the solid electrolyte powder to the fully dispersed glue for homogenization, and then using a scraper with a gap to evenly scrape the solid electrolyte slurry on the surface of the substrate, and finally removing the solvent by heating and drying. In the process of preparing solid electrolyte membranes by wet method, the solid electrolyte will react with the organic solvent, resulting in the ionic conductivity of the solid electrolyte being lower than that of the solid electrolyte powder. At the same time, the use of organic solvents will cause environmental pollution and toxic gases to harm the human body, and the energy consumption is also large during the solvent removal and drying process. Unlike the wet method, the preparation of solid electrolyte membranes by dry method does not require organic solvents at all. It is an environmentally friendly green process and saves production costs such as materials, time and labor. The dry method for preparing solid electrolyte membranes only requires mixing and fiberizing the binder with the solid electrolyte powder. The binder changes from agglomerates to fibrils under a certain temperature and shear force, and the fibrils are meshed to bond the electrode powder to form a whole. The dry binders currently used are mainly polytetrafluoroethylene and its improved polymers, but polytetrafluoroethylene is unstable at low potential and will undergo irreversible reaction with lithium. When polytetrafluoroethylene is used in the solid electrolyte membrane, the side in contact with the negative electrode will consume active lithium during the negative electrode lithiation process, reducing the bonding effect, causing the solid electrolyte membrane to become loose and collapsed, and the solid-state battery structure to be damaged, leading to battery failure. Summary of the invention
[0005] In view of this, the present invention is committed to providing a solid electrolyte membrane and a preparation method and a battery thereof, so as to solve the problem in the prior art that the dry binder is unstable at low potential and easily undergoes irreversible reaction with lithium, thereby reducing the bonding effect and causing the solid electrolyte membrane to become loose and collapsed.
[0006] In order to solve the above technical problems, this application is implemented as follows:
[0007] A first aspect of the present invention provides a solid electrolyte membrane, the solid electrolyte membrane comprising a sulfide solid electrolyte and a binder;
[0008] The binder comprises a copolymerized polyimide spider silk membrane, wherein the molecular weight of the copolymerized polyimide spider silk membrane is 5000 to 73000 g / mol and the density is 1.0 to 1.1 g / cm 3 , the melt index is 50-90MI, and the melting temperature is 90-110℃.
[0009] Optionally, the copolymerized polyimide spider silk membrane has a molecular weight of 7000 to 11000 g / mol and a melt index of 70 to 90 MI.
[0010] Optionally, the ionic conductivity of the sulfide solid electrolyte is ≥6mS / cm; Optionally, the sulfide solid electrolyte includes (1+x)Li2S·xP2S5, Li 6-y PS 5-y X 1+y and Li 11-z M 2-z P 1+z S 12 At least one of, wherein 0<x<1, 0≤y≤0.6, 0.5≤z≤1.5; X is a halogen element, and M is selected from at least one of the elements of Group IVA; optionally, X is selected from at least one of Cl, Br and I; and M is selected from at least one of Ge, Sn and Si.
[0011] Optionally, based on the total mass of the solid electrolyte membrane, the content of the copolymerized polyimide spider silk membrane is 1 to 10 wt %.
[0012] Optionally, the thickness of the solid electrolyte membrane is 50-55 μm; and / or the particle size D50 of the sulfide solid electrolyte is 1-80 μm, preferably 5-30 μm.
[0013] A second aspect of the present invention provides a method for preparing a solid electrolyte membrane, the method comprising:
[0014] S1, mixing a sulfide solid electrolyte and a binder to obtain a first material;
[0015] S2, extruding the first material to obtain a sheet-like solid electrolyte membrane;
[0016] S3, thinning the sheet-like solid electrolyte membrane;
[0017] The binder comprises a copolymerized polyimide spider silk membrane, wherein the molecular weight of the copolymerized polyimide spider silk membrane is 5000 to 73000 g / mol and the density is 1.0 to 1.1 g / cm 3 , the melt index is 50-90MI, and the melting temperature is 90-110℃.
[0018] Optionally, in step S1, the mixing process is performed in an inert atmosphere; the conditions of the mixing process include: a mixing temperature of 95 to 100° C., and a mixing time of 10 to 20 min.
[0019] Optionally, in step S2, the temperature of the extrusion treatment is 95-100°C; and the thickness of the sheet-like solid electrolyte membrane is 150-240 μm.
[0020] Optionally, in step S3, the thinning process is a rolling process.
[0021] A third aspect of the present invention provides a battery, comprising an electrode assembly, wherein the electrode assembly comprises a positive electrode, a solid electrolyte layer and a negative electrode, and the solid electrolyte layer is the above-mentioned solid electrolyte membrane or a solid electrolyte membrane prepared according to the above-mentioned preparation method.
[0022] Through the above technical solution, the beneficial technical effects of the present invention are:
[0023] (1) The solid electrolyte membrane of the present invention has excellent electrical insulation properties. The volume resistivity of the copolymerized polyimide spider silk membrane used in the present invention is very high, and the breakdown voltage is high. The solid electrolyte membrane prepared using the copolymerized polyimide spider silk membrane can have very low electronic conductivity, which can improve the micro-short circuit phenomenon occurring in solid-state batteries.
[0024] (2) The solid electrolyte membrane of the present invention has a high ionic conductivity. The present invention uses a sulfide solid electrolyte with high ionic conductivity as the main raw material of the solid electrolyte membrane. There is no obvious side reaction between the copolymerized polyimide spider silk membrane and the sulfide electrolyte. The sulfide solid electrolyte membrane after mixed extrusion and calendering can achieve a high ionic conductivity.
[0025] (3) The solid electrolyte membrane of the present invention has high structural strength and adhesion. The copolymerized polyimide spider silk membrane used in the present invention has excellent mechanical properties, high mechanical strength and good toughness. It can be used as a binder to prepare a self-supporting solid electrolyte membrane at a relatively low content, and the solid electrolyte structure is kept intact by relying on high toughness and adhesion during the battery charging and discharging process.
[0026] (4) The copolymerized polyimide spider silk membrane used in the present invention has a lower gram weight and can improve the energy density of the battery. The lower operating temperature, operating pressure and pressing time of the copolymerized polyimide spider silk membrane make the solid electrolyte membrane easy to manufacture and produce.
[0027] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0028] The present invention discloses a solid electrolyte membrane and a method for preparing the same and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0029] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] In order to solve the problem in the prior art that the dry binder is unstable at low potential and easily undergoes irreversible reaction with lithium, thereby reducing the bonding effect and causing the solid electrolyte membrane to become loose and collapsed, the present invention adopts the following technical solution:
[0035] A first aspect of the present invention provides a solid electrolyte membrane, the solid electrolyte membrane comprising a sulfide solid electrolyte and a binder;
[0036] The binder comprises a copolymerized polyimide spider silk membrane, wherein the molecular weight of the copolymerized polyimide spider silk membrane is 5000 to 73000 g / mol and the density is 1.0 to 1.1 g / cm 3 , the melt index is 50-90MI, and the melting temperature is 90-110℃.
[0037] In the description of the present invention, the term "melt index (MI)" refers to: the weight value of the melt of thermoplastics passing through a standard capillary within ten minutes at a certain temperature and pressure, expressed in (g / 10min). The larger the MI value, the lower the viscosity and average molecular weight of the raw material, the better the processing performance and the better the fluidity; on the contrary, the smaller the MI value, the larger the viscosity and average molecular weight of the raw material, the worse the processing performance and the worse the fluidity, but the higher the physical and mechanical properties.
[0038] The copolymerized polyimide spider silk membrane (PA spider silk membrane) in the present invention is formed by subjecting the polyimide melt to high voltage static electricity to overcome the surface tension to form a charged jet stream, after which the fibers are solidified, and the nano-scale fibers are arranged in a disordered manner on a collection plate to form a non-woven fiber membrane. The fiber has the characteristics of small fineness and large surface area, and has strength, rigidity and elasticity. The copolymerized polyimide spider silk membrane in the present invention is a filamentous fiber structure, and illustratively, the average silk diameter can be 0.8 to 1.6 μm. The copolymerized polyimide spider silk membrane in the present invention can be obtained commercially, for example: Ketaibo TWA85.
[0039] The copolymerized polyimide spider silk membrane (PA spider silk membrane) in the present invention has a low density and a low melting temperature. Among them, the low density feature can make the prepared solid electrolyte membrane have a low density, thereby improving the energy density of the all-solid-state battery; the low melting temperature feature can reduce the energy consumption of the solid electrolyte membrane preparation process and avoid the conductivity loss of the electrolyte.
[0040] The solid electrolyte membrane of the present invention comprises a sulfide solid electrolyte and a binder, wherein the binder comprises a copolymerized polyimide spider silk membrane. The copolymerized polyimide spider silk membrane is not sticky at room temperature, but undergoes hot-melt bonding at a specific temperature, and can be conveniently transferred and operated during transportation and use. At the same time, an independent self-supporting solid electrolyte membrane can be obtained, and the solid electrolyte structure can be kept intact by relying on high toughness and bonding properties during battery charging and discharging. At the same time, the copolymerized polyimide spider silk membrane is chemically stable with the solid electrolyte powder and the positive and negative electrode sheets, and no obvious side reactions occur, so that the solid electrolyte can still maintain a high ionic conductivity after being prepared into an electrolyte membrane. At the same time, the copolymerized polyimide spider silk membrane has excellent electrical insulation properties, and can effectively block the contact between the positive and negative electrodes.
[0041] In a preferred embodiment of the present invention, the molecular weight of the copolymerized polyimide spider silk membrane can be 7000-11000 g / mol, and the melt index can be 70-90 MI. The copolymerized polyimide spider silk membrane under this molecular weight and melt index can have high processing convenience, and the prepared sulfide electrolyte membrane has excellent lithium ion conductivity and mechanical properties.
[0042] The ionic conductivity of the sulfide solid electrolyte used in the present invention is ≥6mS / cm. By selecting a sulfide solid electrolyte with high ionic conductivity as the main raw material of the solid electrolyte membrane, there is no obvious side reaction between the copolymerized polyimide spider silk membrane and the sulfide electrolyte, so that the solid electrolyte membrane can achieve a higher ionic conductivity. Exemplarily, the sulfide solid electrolyte may include (1+x)Li2S·xP2S5, Li 6-y PS 5-y X 1+y and Li 11-z M 2-z P 1+z S 12 At least one of, wherein 0<x<1, 0≤y≤0.6, 0.5≤z≤1.5; X is a halogen element, and M is selected from at least one of the elements of Group IVA; optionally, X is selected from at least one of Cl, Br and I; and M is selected from at least one of Ge, Sn and Si.
[0043] According to the present invention, based on the total mass of the solid electrolyte membrane, the content of the copolymerized polyimide spider silk net membrane can be 1 to 10wt%. The content of the appropriate copolymerized polyimide spider silk net membrane can increase the structural stability of the solid electrolyte membrane while maintaining the solid electrolyte membrane. Exemplarily, the content of the copolymerized polyimide spider silk net membrane can be any value among 1wt%, 3wt%, 5wt%, 7wt% and 10wt% or any value within the range of any two of the above values. Preferably, the content of the copolymerized polyimide spider silk net membrane can be 2 to 8wt%.
[0044] According to the present invention, the thickness of the solid electrolyte membrane may be 50-55 μm. For example, the thickness of the solid electrolyte membrane may be any value among 50 μm, 51 μm, 52 μm, 53 μm, 54 μm and 55 μm or any value within the range of any two of the above values.
[0045] According to the present invention, the particle size D50 of the sulfide solid electrolyte can be 1 to 80 μm. Exemplarily, the particle size D50 of the sulfide solid electrolyte can be any value among 1 μm, 20 μm, 40 μm, 60 μm and 80 μm or any value within the range of any two of the above values. If the particle size is too large, it may affect the film thickness of the solid electrolyte membrane finally prepared; if the particle size is too small, it may affect the ionic conductivity and performance of the sulfide electrolyte. Preferably, the particle size D50 of the sulfide solid electrolyte is 5 to 30 μm.
[0046] A second aspect of the present invention provides a method for preparing a solid electrolyte membrane, the method comprising:
[0047] S1, mixing a sulfide solid electrolyte and a binder to obtain a first material;
[0048] S2, extruding the first material to obtain a sheet-like solid electrolyte membrane;
[0049] S3, thinning the sheet-like solid electrolyte membrane;
[0050] The binder comprises a copolymerized polyimide spider silk membrane, wherein the molecular weight of the copolymerized polyimide spider silk membrane is 5000 to 73000 g / mol and the density is 1.0 to 1.1 g / cm 3 , the melt index is 50-90MI, and the melting temperature is 90-110℃.
[0051] The present invention uses copolymerized polyimide spider silk net membrane as a binder to prepare a solid electrolyte membrane, wherein the copolymerized polyimide spider silk net membrane has high viscosity in a hot melt state, and a high-density and high-strength solid electrolyte membrane can be obtained by heating, mixing and extruding the materials, and a small pressure (1.5-2.5Kgf / m) is applied after the solid electrolyte membrane prepared by the copolymerized polyimide spider silk net membrane is attached to the positive and negative electrode sheets. 2 ) and lower temperature (90-110℃) can be closely attached to the positive and negative electrodes in a short time (5-15 seconds), simplifying the preparation process of solid-state batteries; at the same time, the copolymerized polyimide spider silk membrane has a lower gram weight range (8-100g / m 2 ), by mixing with solid electrolyte powder, extruding and calendering to form a film, an ultra-thin solid electrolyte membrane with low surface density can be obtained, which can effectively improve the energy density of solid-state batteries.
[0052] According to the present invention, in step S1, in order to avoid the reaction of the sulfide electrolyte with water in the air, the mixing process can be carried out in a dry inert atmosphere, such as dry nitrogen or argon; the temperature of the mixing process in the present invention is slightly higher than the melting temperature of the spider silk membrane, so as to maintain the polyimide spider silk membrane with a certain fluidity, and the temperature of the mixing process is lower than the annealing temperature (200-400°C) of the sulfide solid electrolyte, so as to avoid the sulfide electrolyte from attenuating the ionic conductivity due to re-annealing; the conditions of the mixing process may include: the mixing temperature is 95-100°C, and the mixing time is 10-20min. In an exemplary embodiment of the present invention, the mixing process can be carried out in the hopper of an internal mixer, and a certain amount of sulfide electrolyte and binder are weighed according to the ratio and respectively placed in the preheated internal mixer, and the upper top bolt is dropped for mixing process.
[0053] According to the present invention, in step S2, the temperature of the extrusion treatment can be 95-100°C; the thickness of the sheet-like solid electrolyte membrane can be 150-240 μm. In an exemplary embodiment of the present invention, the extrusion treatment is performed in an extruder, for example, the extruder is a twin-screw extruder, model: Thermo Scientific TM Pharma 16, the screw length of the equipment is 40mm, the diameter is 16mm, the torque is 15Nm / screw, the discharge port is connected to a die head with a slit extrusion port, the extrusion pressure is 150Bar, the slit length is 30mm, the die lip gap is 200μm, and the material obtained by extrusion is 195-200μm because the material will be reduced in thickness due to shrinkage. In an exemplary embodiment of the present invention, the mixed material is added to the extruder to maintain the temperature at 95-100°C, the screw speed is controlled to 20rpm / min, and the screw is waited to extrude the material to the die head. The die head extrusion die head is a flat slit shape with a slit gap of 200μm, and the material is in the form of flakes.
[0054] According to the present invention, in step S3, the thinning process may be a rolling process. In an exemplary embodiment of the present invention, the sheet-like solid electrolyte membrane obtained by extrusion is transferred to a stainless steel roller with a heating device, and the solid electrolyte sheet is repeatedly thinned by adjusting the gap between the upper and lower rollers, and finally a solid electrolyte membrane that meets the thickness requirements can be obtained.
[0055] A third aspect of the present invention provides a battery, comprising an electrode assembly, wherein the electrode assembly comprises a positive electrode, a solid electrolyte layer and a negative electrode, and the solid electrolyte layer is the above-mentioned solid electrolyte membrane or a solid electrolyte membrane prepared according to the above-mentioned preparation method.
[0056] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources. The molecular weight of the copolymerized polyimide spider silk membrane used in the examples is 5500 g / mol and the density is 1.0 g / cm 3 , melt index is 65MI and melting temperature is 95℃.
[0057] Example 1
[0058] (1) Under the protection of argon atmosphere, the internal mixer was started and preheated to 105°C. 45 g of sulfide electrolyte Li6PS5Cl was weighed and placed in the hopper of the internal mixer. 2.37 g of copolymerized polyimide spider silk membrane was added and the top plug was lowered. The mixing was started and the mixing drum speed was adjusted to 20 rpm / min and the mixing was continued for 20 minutes.
[0059] (2) The mixed material is put into the hopper of the extruder, the extruder temperature is set to 100° C., the screw speed is controlled to 20 rpm / min, and the screw is allowed to extrude the material through a die head with a slit gap of 200 μm. The material is discharged as a sulfide electrolyte flake material.
[0060] (3) The temperature of the upper and lower rollers of the electric roller press is set to 100°C for preheating. After the temperature stabilizes, the sulfide electrolyte sheet is bonded to the surface of the lower roller. The roller press operation button is turned on, and the roller speed is adjusted to 5 rpm / min. The gap between the upper and lower rollers is initially adjusted to 150 μm. After the solid electrolyte sheet is rolled once, the gap between the upper and lower rollers is adjusted to 100 μm for the second time, so that the solid electrolyte layer is rolled and thinned again. The gap between the upper and lower rollers is adjusted to 50 μm for the third time. After the sulfide electrolyte membrane is rolled three times, a plastic scraper is used to gently remove the sulfide solid electrolyte membrane from the roller surface and lay it flat on a polytetrafluoroethylene sheet. After natural cooling, a self-supporting sulfide electrolyte membrane with a thickness of 50 to 55 μm can be obtained, which is the solid electrolyte membrane of this embodiment.
[0061] Example 2
[0062] The preparation method of the solid electrolyte membrane of this embodiment is the same as that of Embodiment 1, except that in step (1), the amount of sulfide electrolyte Li6PS5Cl added is 45 g, and the amount of copolymerized polyimide spider silk membrane added is 0.92 g.
[0063] Example 3
[0064] The preparation method of the solid electrolyte membrane of this embodiment is the same as that of Embodiment 1, except that in step (1), the amount of sulfide electrolyte Li6PS5Cl added is 45 g, and the amount of copolymerized polyimide spider silk membrane added is 3.91 g.
[0065] Example 4
[0066] The preparation method of the solid electrolyte membrane of this embodiment is the same as that of Embodiment 1, except that in step (1), the amount of sulfide electrolyte Li6PS5Cl added is 45 g, and the amount of copolymerized polyimide spider silk membrane added is 5 g.
[0067] Comparative Example 1
[0068] In this comparative example, polytetrafluoroethylene (PTFE) is used as a dry binder, and the sulfide electrolyte used is Li6PS5Cl. The proportion of polytetrafluoroethylene in the raw material is shown in Table 1. The process flow is as follows: Under the protection of argon atmosphere, 19g of sulfide electrolyte Li6PS5Cl and 1g of polytetrafluoroethylene (PTFE) are weighed and put into an agate mortar, and the mixture is ground for 20 minutes to obtain a block sulfide electrolyte material. The material is placed on an electric roller press with a heating function, and the temperature of the upper and lower rollers is set to 95°C. The thickness of the material is reduced in batches by adjusting the gap between the upper and lower rollers for multiple times, and the roller gap is finally controlled to be 50μm. After the roller pressing is completed, the sulfide solid electrolyte membrane is removed.
[0069] Comparative Example 2
[0070] The sulfide electrolyte membrane was prepared by wet method. The binder was polypropylene carbonate (manufacturer Aladdin, number average molecular weight 50000). Polypropylene carbonate was dissolved in solvent ethyl acetate. The binder was dissolved by homogenizer at a speed of 200rpm / min for 6h. After the gel was completely dissolved, solid electrolyte particles Li6PS5Cl were added thereto. The homogenizer was used at a speed of 300rpm / min for 40min. The slurry was stirred and dispersed in an inert atmosphere. The solid content of the slurry was 50%. Among the solid substances, the binder accounted for 3%. After the slurry is stirred and dispersed, the solid electrolyte slurry is pipetted and spread on the surface of the aluminum foil on the flat coater, and the scraper gap is adjusted to 110 μm for scraping, and the scraping speed is 2 m / min. After the scraping is completed, the heating of the flat coater is turned on, and the coated area is dried at a temperature of 60°C for 20 minutes. After the surface is completely dry, the aluminum foil substrate with the sulfide electrolyte membrane is transferred to a vacuum oven for secondary drying at a drying temperature of 90°C for 12 hours. After drying, the solid electrolyte membrane of this comparative example is obtained.
[0071] Comparative Example 3
[0072] Commercial PA-6 powder is used as a binder for dry sulfide electrolyte membrane. The particle size of PA-6 powder is about 50 μm. The specific information is shown in Table 1. The process is as follows:
[0073] (1) Under the protection of argon atmosphere, the internal mixer was started and preheated to 105°C. 45 g of sulfide electrolyte Li6PS5Cl was weighed and placed in the hopper of the internal mixer. 5 g of PA-6 powder was added and the top plug was lowered. The mixing was started and the mixing drum speed was adjusted to 20 rpm / min. The mixing was continued for 20 minutes.
[0074] (2) The mixed material is put into the hopper of the extruder, the extruder temperature is set to 100° C., the screw speed is controlled to 20 rpm / min, and the screw is allowed to extrude the material through a die head with a slit gap of 200 μm. The material is discharged as a sulfide electrolyte flake material.
[0075] (3) The temperature of the upper and lower rollers of the electric roller press is set to 100°C for preheating. After the temperature stabilizes, the sulfide electrolyte sheet is bonded to the surface of the lower roller. The roller press operation button is turned on, and the roller speed is adjusted to 5 rpm / min. The gap between the upper and lower rollers is initially adjusted to 150 μm. After the solid electrolyte sheet is rolled once, the gap between the upper and lower rollers is adjusted to 100 μm for the second time, so that the solid electrolyte layer is rolled and thinned again. The gap between the upper and lower rollers is adjusted to 50 μm for the third time. After the sulfide electrolyte membrane is rolled three times, a plastic scraper is used to gently remove the sulfide solid electrolyte membrane from the roller surface and lay it flat on a polytetrafluoroethylene sheet. After natural cooling, a self-supporting sulfide electrolyte membrane with a thickness of 50-55 μm can be obtained, which is the solid electrolyte membrane of this comparative example.
[0076] Table 1
[0077]
[0078] Test Example 1
[0079] The conductivity of the solid electrolyte membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was tested. The test results are shown in Table 2.
[0080] A solid-state battery was prepared using the solid electrolyte membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 as the solid electrolyte layer, and a cycle performance test was performed on the prepared solid-state battery. The test results are shown in Table 2.
[0081] Among them, the conductivity test method includes: sampling the solid electrolyte membrane through a circular sampler with a diameter of 10mm, gently placing the circular sample to be tested in an insulating sleeve with an inner diameter of 10mm, attaching smooth aluminum foil on the top and bottom of the solid electrolyte membrane, installing a plug and pressurizing it at a pressure of 300MPa, and performing an AC impedance spectrum test to measure the impedance value of the sulfide solid electrolyte membrane material. Then, the thickness of the pressurized sheet sulfide solid electrolyte membrane is tested, and the ionic conductivity of the electrolyte material is calculated according to the impedance value, thickness value and area of the pressed sheet by the formula σ=d / (R*S), where σ is the ionic conductivity, unit s / cm; d is the thickness of the pressed sheet, unit cm; R is the impedance value, unit Ω; S is the area of the pressed sheet, unit cm 2 The test results are shown in Table 2.
[0082] The preparation method of the solid-state battery comprises: in an argon glove box, a sulfide electrolyte Li6PS5Cl, a positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1)O2(NCM811) were weighed at a weight ratio of 20:80. They were ground evenly using an agate mortar to produce a composite positive electrode material. In an insulating outer cylinder with a diameter of 10 mm, 14 mg of the above-mentioned composite positive electrode material and the sulfide solid electrolyte membrane to be tested were stacked. Then, on the opposite side of the solid electrolyte membrane that was in contact with the positive electrode, a lithium indium composite sheet with a thickness and diameter of 200 μm and 10 mm, respectively, was placed as a negative electrode material. It was press-formed at a pressure of 80 MPa to produce a composite structure consisting of a positive electrode, a solid electrolyte membrane and a negative electrode. The wires were connected to the upper and lower column leads of stainless steel to obtain a solid-state battery. The assembled solid-state battery was subjected to a cycle performance test under the following test conditions: a current density of 1C and a voltage range of 2.0-3.7V (Li+ / Li).
[0083] Among them, the test method of the first coulombic efficiency includes: using a laboratory charge and discharge tester to perform a charge and discharge test on the battery, and dividing the first week discharge capacity by the first week charge capacity to calculate the first coulombic efficiency.
[0084] The test method of the first-week discharge capacity includes: dividing the first discharge capacity by the mass of the positive electrode active material in the battery to calculate the first-week discharge specific capacity.
[0085] The test method for the capacity retention rate after 100 cycles includes: setting the charge and discharge steps of the laboratory buckle charge and discharge tester to: 1C constant current charging, voltage cutoff to 3.7V, standing for 5 minutes, 1C constant current discharge, voltage cutoff to 2.0V, standing for 5 minutes, the above steps are charged and discharged once as one cycle, the cycle is repeated 100 times, and the capacity retention rate is calculated by dividing the capacity of the 100th discharge by the capacity of the first discharge.
[0086] The test method of the cycle average coulombic efficiency includes: calculating the average coulombic efficiency in 100 charge and discharge cycles to obtain the cycle average coulombic efficiency.
[0087] Table 2
[0088]
[0089] Combining the data in Table 1 and Table 2, it can be seen from Examples 1 to 4 and Comparative Examples 1 to 3 that as the content of the dry binder increases, the ionic conductivity of the sulfide solid electrolyte membrane shows a downward trend. When the binder content is ≥8%, the ionic conductivity of the sulfide solid electrolyte membrane prepared by the dry binder is basically consistent with the solid electrolyte membrane prepared by the wet process. When the binder content reaches 10%, the ionic conductivity of the solid electrolyte membrane is only 1.1 mS / cm, indicating that at this time the sulfide electrolyte particles may be partially wrapped by a higher content of binder, and a layer of electronic and ion insulating binder is separated between the electrolyte particles, which directly affects the conduction of lithium ions. Therefore, the conductivity of the prepared dry sulfide electrolyte membrane decreases significantly. When the binder content is 2%, although the ionic conductivity of the sulfide electrolyte membrane is the highest, its strength is lower than that of other sulfide solid electrolyte membranes prepared by the dry process due to the lower binder content, which increases the difficulty of battery assembly. The sulfide electrolyte membrane is assembled in the battery to characterize the battery performance. From the data in Table 2, it can be seen that the first-cycle discharge performance of the battery assembled with the sulfide electrolyte membrane prepared by the dry method is better than that of the battery assembled with the sulfide solid electrolyte membrane prepared by the wet method in Comparative Example 2, and the first efficiency can reach more than 91%; the battery cycle performance test of the above embodiments and comparative examples is carried out. After 100 cycles, the capacity decay of the battery assembled with the sulfide electrolyte membrane prepared by the dry method is significantly lower than that of the wet membrane battery, mainly because the side reaction of the solvent on the solid electrolyte is avoided; at the same time, it can be seen from the comparison between Examples 1 to 4 and Comparative Example 1 that the cycle performance is significantly improved. In Comparative Example 1, due to the use of polytetrafluoroethylene as a binder, its reaction with lithium on the negative electrode side causes partial failure during the cycle process, while the PA spider silk membrane used in the embodiment is used as a dry binder. Thanks to its excellent stability with the electrolyte, positive and negative electrodes, it achieves lower capacity decay, and its good electrical insulation performance also brings excellent Coulombic efficiency indicates that the battery has less low coulombic efficiency due to self-discharge during the cycle, which further indicates that the battery cycle stability can be improved by using PA spider silk membrane as a binder for the solid electrolyte membrane; Comparative Example 3 uses PA-6 powder as a binder. Since both the powder and the sulfide electrolyte powder are powders, PA powder is easily wrapped on the surface of part of the sulfide electrolyte powder during the mixing process, thereby preventing the transmission of lithium ions. The data during the lithium ion conductivity test is only 0.8mS / cm. Similarly, the electrolyte membrane has a long constant voltage section during the charging process after being assembled into a battery, and the discharge capacity is low, with a coulombic efficiency of only 88%, which is lower than the performance of other PA spider silk membranes in sulfide electrolyte membranes. The original form of the spider silk membrane is fibrous, and there will be no obvious coating phenomenon during the mixing process with the sulfide electrolyte. Instead, the fiber viscosity is used to bond the sulfide electrolyte particles, which ensures both the ion transmission channel and the mechanical strength of the film.
[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane includes a sulfide solid electrolyte and a binder; The binder comprises a copolymerized polyimide spider silk membrane, wherein the molecular weight of the copolymerized polyimide spider silk membrane is 5000 to 73000 g / mol and the density is 1.0 to 1.1 g / cm 3 , the melt index is 50-90MI, and the melting temperature is 90-110℃.
2. The solid electrolyte membrane according to claim 1, characterized in that The molecular weight of the copolymerized polyimide spider silk membrane is 7000-11000 g / mol, and the melt index is 70-90 MI.
3. The solid electrolyte membrane according to claim 1, characterized in that The ionic conductivity of the sulfide solid electrolyte is ≥6mS / cm; Optionally, the sulfide solid electrolyte includes (1+x)Li2S·xP2S5, Li 6-y PS 5-y X 1+y and Li 11-z M 2-z P 1+ z S 12 At least one of the following, wherein 0<x<1, 0≤y≤0.6, 0.5≤z≤1.5; X is a halogen element, and M is selected from at least one of the elements of Group IVA; Optionally, X is selected from at least one of Cl, Br and I; and M is selected from at least one of Ge, Sn and Si.
4. The solid electrolyte membrane according to claim 1, characterized in that Based on the total mass of the solid electrolyte membrane, the content of the copolymerized polyimide spider silk membrane is 1-10wt%.
5. The solid electrolyte membrane according to claim 1, characterized in that The thickness of the solid electrolyte membrane is 50-55 μm; And / or, the particle size D50 of the sulfide solid electrolyte is 1 to 80 μm, preferably 5 to 30 μm.
6. A method for preparing a solid electrolyte membrane, characterized in that: The preparation method comprises: S1, mixing a sulfide solid electrolyte and a binder to obtain a first material; S2, extruding the first material to obtain a sheet-like solid electrolyte membrane; S3, thinning the sheet-like solid electrolyte membrane; The binder comprises a copolymerized polyimide spider silk membrane, wherein the molecular weight of the copolymerized polyimide spider silk membrane is 5000 to 73000 g / mol and the density is 1.0 to 1.1 g / cm 3 , the melt index is 50-90MI, and the melting temperature is 90-110℃.
7. The preparation method according to claim 6, characterized in that: In step S1, the mixing process is performed in an inert atmosphere; the conditions of the mixing process include: a mixing temperature of 95 to 100° C. and a mixing time of 10 to 20 min.
8. The preparation method according to claim 6, characterized in that: In step S2, the temperature of the extrusion treatment is 95-100°C; the thickness of the sheet-like solid electrolyte membrane is 150-240 μm.
9. The preparation method according to claim 6, characterized in that: In step S3, the thinning process is a rolling process.
10. A battery, characterized in that: The battery comprises an electrode assembly, wherein the electrode assembly comprises a positive electrode, a solid electrolyte layer and a negative electrode, and the solid electrolyte layer is a solid electrolyte membrane according to any one of claims 1 to 5 or a solid electrolyte membrane prepared by the preparation method according to any one of claims 6 to 9.